Bubble dynamics and size distributions during focused ultrasound insonation - Yang, X; Roy, R; Holt, R (Acoustical Society of America, 2004)
The deposition of ultrasonic energy in tissue can cause tissue damage due to local heating. For pressures above a critical threshold, cavitation will occur, inducing a much larger thermal energy deposition in a local region. The present work develops a nonlinear bubble dynamics model to numerically investigate bubble oscillations and bubble-enhanced heating during focused ultrasound (HIFU) insonation. The model is applied to calculate two threshold-dependent phenomena occurring for nonlinearly oscillating bubbles: Shape instability and growth by rectified diffusion. These instabilities in turn are shown to place physical boundaries on the time-dependent bubble size distribution, and thus the thermal energy deposition.